Characteristics and related mechanisms of the persistent extreme precipitation in August 2020 over Western China - Qianrong, Ma; Fang, Jia; Xiaoxue, Wu; Youzhi, Chang; Rong, Zhi; Guoling, Feng (Frontiers in Earth Science, 2022)
The persistent heavy precipitation that occurred in most of West China (WC) during August 11–18, 2020, generated the highest rainfall record since recording began in 1961 and was selected as one of the top 10 worst national natural disasters of 2020 in China. Favorable circulation was sustained during August; WC was positioned between two anomalous high-pressure centers over the Tibetan Plateau and Sea of Japan and an anomalous low-pressure center over Mongolia located on its north side, which created a stable and long trough and formed a low-pressure center over WC. At 200 hPa, the subtropical westerly jet was much stronger than average and southward, and the South Asian High (SAH) was strong and extended eastward to 150°E. At 500 hPa, the western Pacific subtropical high (WPSH) was westward and exceptionally strong, which helped abundant water vapor reach the southeastern part of WC and provided favorable dynamic and thermodynamic conditions for precipitation in this region. In addition, the eastward extension of the SAH promotes the westward extension of WPSH, which collectively enhanced the precipitation in WC. At 850 hPa, the low-level jet corresponding to the west-extending subtropical high from the Sea of Japan to WC further enhanced and guided the water vapor transport to WC. In addition, the Mei-Yu front over the Yangtze River Basin in June and July strengthened the northwestward spread of diabatic heating, transient energy, and wave activity fluxes, which likely influenced the large-scale circulation factors and reinforced the precipitation in WC in August 2020.